2019
DOI: 10.1186/s13023-019-1033-5
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for etoposide in the treatment of pregnancy related hemophagocytic lymphohistiocytosis: a multicenter retrospective study

Abstract: Background Hemophagocytic lymphohistiocytosis (HLH) is a rare severe clinical syndrome. HLH manifesting during pregnancy has been paid much attention in recent years. Despite the specificity of pregnancy-related HLH, there has not been any consensus regarding its treatment. According to a previous study, corticosteroid/IVIG is the mainstream therapy; however, the efficacy is controversial. Etoposide is an important agent in the HLH-94 regimen; nevertheless, its use is limited because of possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…However, studies by several scholars [ 7 , 38 , 39 ] have shown that the use of etoposide would be of more benefit to the patient than harm to the foetus. Song et al [ 40 ] suggested that achieving a balance between effective treatment and foetal safety was critical. Etoposide should be used actively but at appropriate doses and low toxicity.…”
Section: Main Textmentioning
confidence: 99%
“…However, studies by several scholars [ 7 , 38 , 39 ] have shown that the use of etoposide would be of more benefit to the patient than harm to the foetus. Song et al [ 40 ] suggested that achieving a balance between effective treatment and foetal safety was critical. Etoposide should be used actively but at appropriate doses and low toxicity.…”
Section: Main Textmentioning
confidence: 99%
“…Previous case series have documented flares in the first and second trimesters and postpartum period, with greatest incidence in the second trimester ( 10 , 11 ). HLH/MAS of other causes has occasionally been reported in the third trimester but also seems disproportionately to favor the second trimester and postpartum period ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…No neonatal malformations have been reported [34]. Song et al [27] reported the use of etoposide in a pregnant patient with HLH. No congenital malformations were found in the fetus.…”
Section: Discussionmentioning
confidence: 99%